Rational Design of an Ionic Liquid‐Based Electrolyte with High Ionic Conductivity Towards Safe Lithium/Lithium‐Ion Batteries. Issue 16 (24th July 2019) - Zhang, Shengjie; Li, Junhao; Jiang, Ningyi; Li, Xuqiu; Pasupath, Sivakumar; Fang, Yanxiong; Liu, Quanbing; Dang, Dai
Abstract: It is a very urgent and important task to improve the safety and high‐temperature performance of lithium/lithium‐ion batteries (LIBs). Here, a novel ionic liquid, 1‐(2‐ethoxyethyl)‐1‐methylpyrrolidinium bis(trifluoromethylsulfonyl)imide (PYR1(2o2) TFSI), was designed and synthesized, and then mixed with dimethyl carbonate (DMC) as appropriate solvent and LiTFSI lithium salt to produce an electrolyte with high ionic conductivity for safe LIBs. Various characterizations and tests show that the highly flexible ether group could markedly reduce the viscosity and provide coordination sites for Li‐ion, and the DMC could reduce the viscosity and effectively enhance the Li‐ion transport rate and transference number. The electrolyte exhibits excellent electrochemical performance in Li/LiFeO4 cells at room temperature as well as at a high temperature of 60 °C. More importantly, with the addition of DMC, the IL‐based electrolyte remains nonflammable and appropriate DMC can effectively inhibit the growth of lithium dendrites. Our present work may provide an attractive and promising strategy for high performance and safety of both lithium and lithium‐ion batteries. Abstract : A novel ionic liquid, 1‐(2‐ethoxyethyl)‐1‐methylpyrrolidinium bis(trifluoromethylsulfonyl)imide (PYR1(2o2) TFSI), was designed and synthesized, and then mixed with dimethyl carbonate (DMC) as appropriate solvent and LiTFSI lithium salt to produce an electrolyte with high ionic conductivity for safe LIBs. The IL‐based electrolyte exhibits excellent electrochemical performance in Li/LiFeO4 cells at room temperature as well as at a high temperature of 60 °C. The flexible ether group can markedly reduce the viscosity and provide coordination sites for Li‐ions.